The Implementation of Group Investigation Model on Learning Outcome at The Topic Ecosystem Class X In SMA Negeri 11 Medan Academic Year 2014/2015 - Farahnaz Afriliandini; Meida Nugrahalia (Universitas Negeri Medan, 2015)
This research was carried out to find out The Implementation of GroupInvestigation Model on Learning Outcomes at The Topic Ecosystem Class X in SMANegeri 11 Medan Academic Year 2014/2015. Therefore, an experimental researchwas carried as the research as a research design. The population was 2014/2015academic years students, in the second years students of SMAN 11 Medan,especially the students of class X which consisted of 320 students. From thepopulation was taken 80 students as the sample by using Random Sampling. Theywere divided into two groups, 40 students in experimental groups taught by usinggroup investigation model and 40 students in control group taught by using directinstruction.Based on the result of research obtained the mean pretest in class control44.8 and experimental class 51.7, this shows the initial ability of the both classes issame similarity. Then the both of classes were given a different treatment, theexperimental class used Group Investigation and control class used DirectInstruction. After the learning had finished, the both of classes given posttest ofcontrol class 77.9 and experimental class 81.75.The result test t obtained that t count >t table (2.03 < 1.66) then H0 is rejected and Ha accepted. Furthermore, based onpercentage of students activity showed that students in experimental class more activethan class control. It can be conclude that is effect of group investigation learningoutcomes on students at topic ecosystem in class X SMA Negeri 11 Medan AcademicYear 2014/2015.Key words: group investigation model, learning outcome, activity